2018
DOI: 10.1002/mp.12827
|View full text |Cite
|
Sign up to set email alerts
|

Geant4‐DNA track‐structure simulations for gold nanoparticles: The importance of electron discrete models in nanometer volumes

Abstract: Improved physics models for gold are necessary to better model the impact of GNPs in radiotherapy via Monte Carlo simulations. We implemented discrete electron transport models for gold in Geant4 that is applicable down to 10 eV including the modeling of the full de-excitation cascade. It is demonstrated that the new model has a significant positive impact on particle transport simulations in gold volumes with submicron dimensions compared to the existing Livermore and Penelope condensed-history models of Gean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 72 publications
1
48
0
Order By: Relevance
“…For interactions of electrons in gold, discrete physics models for electron transportation down to 10 eV have recently been implemented within the Geant4-DNA low energy extension of Geant4. Such models allow the investigation of GNP effects at the nanoscale [54,55]. For practical MC radiation transport simulations, elastic scattering, excitation and ionization cross sections for electrons were calculated for water vapor, liquid water and DNA molecular moiety to mimic the interactions of electrons in biological tissues [42,53,[56][57][58].…”
Section: Physical Interaction Of Electrons With Gold and Liquid Watermentioning
confidence: 99%
See 1 more Smart Citation
“…For interactions of electrons in gold, discrete physics models for electron transportation down to 10 eV have recently been implemented within the Geant4-DNA low energy extension of Geant4. Such models allow the investigation of GNP effects at the nanoscale [54,55]. For practical MC radiation transport simulations, elastic scattering, excitation and ionization cross sections for electrons were calculated for water vapor, liquid water and DNA molecular moiety to mimic the interactions of electrons in biological tissues [42,53,[56][57][58].…”
Section: Physical Interaction Of Electrons With Gold and Liquid Watermentioning
confidence: 99%
“…The most widely used physics lists of interactions in GNPs are the so-called Livermore and Penelope lists. Both lists use condensed-history models for electron transport and were shown to underestimate the backscattering coefficients compared to yet unreleased discrete models [54,55]. The Livermore physics list can be used down to 10 eV [54,82] (while not recommended), but the Penelope list has a limit at 100 eV and was found to underestimate dose enhancement within the first 100 nm from a GNP surface [83].…”
Section: A2 Topas/topas-nbio Codementioning
confidence: 99%
“…The physics model of electron interaction in gold may have an impact on the simulation results. It is worth noting that besides the Livermore physics for gold, there are some improved models for gold to better predict the impact of GNPs, such as the discrete models (Geant4‐DNA‐AU) for electron transport in gold in Geant4 which are applicable down to 10 eV including the modeling of the full‐excitation . It was found that new discrete model for gold shows similar backscattering coefficient to the existing Geant4 Livermore model, but in submicron‐sized volumes, only the discrete physics models describe the high backscattering presenting around GNPs.…”
Section: Resultsmentioning
confidence: 99%
“…These models, which adopt either the dielectric response function approach or other hybrid approaches, undergo continuous development and refinement. Recently, track-structure models for gold nanoparticles have also been developed and will be incorporated in the upcoming Geant4-DNA releases [83][84][85]. It also includes modelling of the chemical stage [86] and offers various representations of DNA target structures to be used in DNA damage studies [87][88][89].…”
Section: Particle Track Structure Codesmentioning
confidence: 99%